2013
DOI: 10.4103/0378-6323.115505
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of psoriasis

Abstract: Psoriasis is a chronic inflammatory papulosquamous disease characterized by multiple remissions and relapses. For long, it was believed to be primarily a disorder of keratinization. However, the successful use of traditional immunosupressants and newer immunomodulatory agents in the treatment of psoriasis led to the belief that psoriasis is primarily a disease of Th1 cell immune dysregulation. Recent developments have brought up several new findings such as the role of Th17 cells and evidence of skin barrier d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 63 publications
0
12
0
1
Order By: Relevance
“…Consequent to extensive ongoing research in this field, new factors are constantly being added to the cascade of events that lead to the formation of psoriatic plaques. 1 3 A brief note on the role of immune cells in the pathogenesis of psoriasis is mentioned in this section, in the paragraph below.…”
Section: Role Of Immune Cells and Co-stimulatory Signals In Pathogenementioning
confidence: 99%
See 1 more Smart Citation
“…Consequent to extensive ongoing research in this field, new factors are constantly being added to the cascade of events that lead to the formation of psoriatic plaques. 1 3 A brief note on the role of immune cells in the pathogenesis of psoriasis is mentioned in this section, in the paragraph below.…”
Section: Role Of Immune Cells and Co-stimulatory Signals In Pathogenementioning
confidence: 99%
“…Recent studies show that, in addition to T lymphocytes, keratinocytes also play a major role in the cutaneous immune response of psoriasis. 1 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…A complex interaction between the innate immunity, adaptive immunity and a skin barrier defect is likely to explain the possible pathogenesis of psoriasis, though the response of the disease to biological response modifiers points primarily towards the role of adaptive immunity in causation. [ 7 ] Though exact cause in not known, oxidative stress has been widely implicated in the pathogenesis of psoriasis. It has been suggested that generation of reactive oxygen species (ROS) from neutrophils, keratinocytes, and fibroblasts can contribute to neutrophil activation, which plays an important role in the psoriatic process.…”
Section: Discussionmentioning
confidence: 99%
“…Di Rumah Sakit Umum Pusat (RSUP) H. Adam Malik Medan, berdasarkan data yang diperoleh dari rekam medis selama periode Januari 2010-Desember 2012, 75 kasus merupakan pasien dengan diagnosis psoriasis (Suhoyo et al 2013). Banyak faktor yang dapat mengakibatkan munculnya psoriasis seperti genetik, lingkungan, trauma fisik, stres psikologis, obat obatan dan infeksi (Mahajan & Handa, 2013).…”
Section: Pendahuluanunclassified